Conceptual Study of Technology-Based Learning Media in Internalizing Religious Ethical Values - Muhammad Irfan Izzuddin; Istanto Istanto (Universitas Muhammadiyah Surakarta, 2025)
The increasing moral challenges faced by students in the digital age require educational strategies that are not only cognitively oriented but also capable of fostering a commitment to religious values and ethical behavior. This study aims to formulate a conceptual framework on how technology-based learning media can be designed and implemented pedagogically to internalize religious ethical values in students, by linking the concepts of digital media, value internalization theory, religious character education, and the context of Society 5.0. The method used is a qualitative approach through literature study with content analysis; literature is selected from reputable scientific sources and analyzed thematically to map trends, media forms, success factors, and the potential and challenges of implementation. The results of the study show a shift in the function of technology from merely presenting material to becoming an effective